Nucleocytoplasmic Shuttling of p130/RBL2: Novel Regulatory Mechanism - Chestukhin, Anton (American Society for Microbiology, 2002)
The retinoblastoma-related pocket proteins pRb, p107, and p130 are implicated in the control of cell proliferation, differentiation, and transformation. The function of pocket proteins is in part mediated by their ability to inhibit specific E2F transcription factors. The transcriptional activity of E2Fs is controlled by alteration of their nucleocytoplasmic localization during the cell cycle. p130 was observed to shuttle between the nucleus and cytoplasm in a heterokaryon fusion assay, suggesting the presence of nuclear and cytoplasmic localization signals. Two independent nuclear localization signals (NLS) that could target reporter proteins to the nucleus in transient transfection and microinjection experiments were identified in the C terminus of p130. In addition to the C-terminal NLS, the intact pocket domain of p130 itself was sufficient for nuclear translocation. Moreover, an additional functional NLS was mapped within the unique Loop region of p130. An N-terminal domain that conferred cytoplasmic localization was identified. Removal of the entire N terminus did not affect the ability of p130 to interact with E2F and to induce growth arrest. A model suggesting that the activity of pRb family members can be regulated by intracellular trafficking of the proteins is proposed.